أثر البيئة الطبيعية في الحياة الإجتماعية عند ابن خلدون - صالحي، علي (جامعة الوادي university of Eloued, 2017)
ملخـص الدراسة: تعد علاقة الإنسان بالبیئة علاقة أزلیة ، فمنذ وجوده على هذا الكون وهو صراع دائم مع عناصر النظام البیئي ، و كان دائما یسعى جاهدا نحو إستغلاله للموارد البیئیة في تلبیة حاجیاته الیومیة و المتزایدة ، و للمستوى المعرفي و الفكري لدیه إرتباطا و ثیقا بهذه العلاقة ، و ذلك ما تبرزه الأطوار التاریخیة التي مرت بها ، مما یجعل الأهمیة البالغة للدراسة و البحوث فیها ، و التي كانت منذ الحضارات القدیمة و الإسلامیة منها، حیث كان لابن خلدون السبق في دراسة هذه العلاقة ، مما یجعل من آثاره الفكریة مجالا خصبا للدراسات و التحلیل ، و منه تم طرح التساؤلات فكان الرئیسي منها : - ما هو أثر البیئة الطبیعیة على الحیاة الإجتماعیة الذي تضمنته مقدمة ابن خلدون ؟ و للإحاطـة و الإلمام بموضوع الدراسة إخترنا التساؤلات الفرعیة التالیة : -1ما تأثیر البیئة الطبیعیة على كافة أحوال البشر في مقدمة ابن خلدون ؟ -2ما تأثیر البیئة الطبیعیة على بناء المـدن السكانیة في مقدمة ابن خلدون ؟ -3ما تأثیر البیئة الطبیعیة على تنوع الصنائع و العلوم في مقدمة ابن خلدون ؟ و للإجابة عنها طبق الباحث منهج تحلیل المحتوى على مقدمة ابن خلدون كعینة من مجتمع مكون من جمیع مؤلفاته ، حیث إختار وحدة الفكرة كوحدة للتحلیل مستخدما التكرارات و النسب المئویة كأسلوب إحصائي ، لتكمیم البیانات و عرضها، و بعد ذلك قام الباحث بتحلیل هذه البیانات مما أوصله إلى مجموعة من النتائج نذكر من أهمها : -1حیث یربط ابن خلدون وفور العمران البشري و توزعه على حسب طبیعة إقلیم الأرض و مدى ملائمة مناخه من درجة الحر و البرد لهوائه و إمكانیة تكوینهما . -2یعلل ابن خلدون الإختلاف بین أفراد العمران البشري في لون البشرة تبعا لإختلاف درجة الحر و البرد في الهواء و إختلافها ، مع إمكانیة تغیر لون البشرة بتغیر طبیعة المناخ من حرارة و برودة للهواء بتعاقب الأجیال و أنه لیس صفة وراثیة دائمة . -3یعلل ابن خلدون خراب المدن السكنیة بعدم مراعاة الشروط الضروریة الواجب إتخاذها عند إنشائها،من خصوبة للأرض و طیب للهواء و الماء، و قرب من الجبال و البحر أیضا. -4یربط ابن خلدون بین وجود الصنائع و المهن أو عدمها بدرجة حاجة أفراد العمران البشري لها . -5یؤكد ابن خلدون على العلاقة بین وجود العلوم و تعددها و إختلاف أقالیم الأرض بین المعتدل منها و المنحرف . و في ختام هذه الدراسة قام الباحث بمناقشة النتائج المتحصل علیها ، مما ساعده على وضع مجموعة من التوصیات . Summary of the Study: The relationship between man and environment is an eternal one , Since his existence on this universe , he is constant conflict with elements of the ecosystem, He was always striving to exploit the environmental resources to meet his daily and increasing needs, His cognitive and intellectual level is closely related to this relationship , and this highlighted by the historical phases that passed , which makes the importance of study and research in it , It was from ancient civilizations and the Islamic ones, wher Ibn Khaldoun was first to study of this relationship, and this makes his intellectual effects as a fertile ground for studies and analysis, and from which was raised questions, the main one was : - What is the impact of the natural environment on the social life contained in the introduction of Ibn Khaldoun ? To learn more about the subject , we have chosen the following sub-sectional questions : 1. What is the impact of the natural environment on all human conditions in Ibn Khaldun's introduction? 2. What is the impact of the natural environment on building the population cities in Ibn Khaldun's introduction? 3. What is the impact of the natural environment on diversity of industry and science in Ibn Khaldun's introduction? The researcher applied the method of content analysis to Ibn Khaldun's introduction as a sample of a society composed of all his works , He chose the unity of the idea as a unit of analysis using repetitions and percentages as a statistical method to quantify the data and display them , After that , The researcher analyzed these data which led to a set of results , the most important ones are: 1. Where the Ibn Khaldoun connects the a bun dance of human construction and its distribution according to the nature of the territory of the earth and the entent to which its climate is suitable for the degree of heat coldness of its atmosphere at the possibility of their composition .2. Ibn Khaldoun explains the difference between human beings in the skin color depending on the degrees of temperature and coldness in the air and its difference with the possibility of changing the color of the skin by changing the nature of climate of heat and coldness of the air in sequence of generations and it is not permanent genetic train . 3. Ibn Khaldoun explain the destruction of residential cities by not necessary conditions that must be taken at the time of its establishment , from fertility to land and good for air water , and near the mountains and the sea also . 4. Ibn Khaldoun connects the existence of trades occupations or not , to the entent that human beings need them . 5. Ibn Khaldoun emphasizes the relationship between the esustence and diversity of science and the difference between the regions of the land between the moderate and the deviant from them . At the conclusion of this study, the researcher discussed the results obtained, which helped him to put a set of recommendations.
دراسة تحليلية لمحتوى المقدمة
مذكرة ماستر علوم إجتماعية تخصص علم إجتماع البيئة
Keywords: البيئة الطبيعية، ابن خلدون; Environnement naturel, Ibn Khaldoun; Environnement naturel, Ibn Khaldoun